Ms. Rachel and the special surprise : encouraging speech and learning through play and music - Accurso, Rachel (Random House Children's Books, 2024)
"Ms. Rachel is looking for something very special, and she needs your help finding it! With more than 20 important milestones featured--including gestures and speech--Ms. Rachel brings educational expertise to her debut picture book. Using key lessons from her YouTube channel and threading them into an interactive story, she shows kids and parents alike fun ways to engage and play!"--